Clinical and Echocardiographic Outcomes of Transcatheter Tricuspid Valve Interventions: A Systematic Review and Meta-Analysis - Sannino, Anna; Ilardi, Federica; Hahn, Rebecca T.; Lancellotti, Patrizio; Lurz, Philipp; Smith, Robert L.; Esposito, Giovanni; Grayburn, Paul A. (Frontiers in Cardiovascular Medicine, 2022)
Background Medically managed tricuspid regurgitation (TR) has detrimental outcomes. Transcatheter tricuspid valve interventions (TTVIs) represent an alternative to surgery in high-risk patients; however, only early experiences exist. Aim The aim of this study was to analyze the clinical and echocardiographic outcomes of TTVI. Methods MEDLINE, ISI Web of Science, and SCOPUS databases were searched for studies published up to June 2021. Studies reporting data on outcome post-TTVIs were included. This study was designed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) requirements. The primary endpoint was all-cause mortality at 30-day and 1-year post-TTVI. Results Out of 2,718 studies, 27 were included. Notably, 30-day and 1-year all-cause mortalities were 5% (95% confidence interval [CI]: 4–8%, p < 0.001) and 25% (95% CI: 12–45%, p = 0.016). Procedural success was associated with a 58% risk reduction in 1-year mortality vs. lack thereof (odds ratio 0.42, 95% CI: 0.27–0.66, p < 0.001). TTVI is associated with a significant reduction in TR severity (TR EROA, mean difference [MD] 0.31 cm2; 95% CI: 0.23–0.39 cm2, p < 0.001; regurgitant volume, MD 23.54 ml; 95% CI: 17.4–29.68 ml, p = 0.03) and increase in forward stroke volume (FSV, MD 3.98 ml; 95% CI: 0.11–7.86 ml, p = 0.04). Conclusion TTVI significantly reduces TR severity and increases FSV and is associated with improved survival at 1 year compared with patients without procedural success. Long-term outcomes compared with medical therapy await the results of ongoing pivotal trials; nonetheless, TTVIs appear to be a promising alternative to surgery for TR.